Dietary intake of advanced glycation end products (AGEs) and changes in body weight in European adults - Cordova, R; Knaze, V; Viallon, V; Rust, P; Schalkwijk, C; Weiderpass, E; Wagner, K; Mayen-Chacon, A; Aglago, E; Dahm, C; Overvad, K; Tjønneland, A; et al. (Springer, 2019)
Purpose: Advanced glycation end products (AGEs) can be formed in foods by the reaction of reducing sugars with proteins, and have been shown to induce insulin resistance and obesity in experimental studies. We examined the association between dietary AGEs intake and changes in body weight in adults over an average of 5 years of follow-up. Methods: A total of 255,170 participants aged 25–70 years were recruited in ten European countries (1992–2000) in the PANACEA study (Physical Activity, Nutrition, Alcohol, Cessation of smoking, Eating out of home in relation to Anthropometry), a sub-cohort of the EPIC (European Prospective Investigation into Cancer and Nutrition). Body weight was measured at recruitment and self-reported between 2 and 11 years later depending on the study center. A reference database for AGEs was used containing UPLC–MS/MS-measured Nε-(carboxymethyl)-lysine (CML), Nε-(1-carboxyethyl)-lysine (CEL), and Nδ-(5-hydro-5-methyl-4-imidazolon-2-yl)-ornithine (MG-H1) in 200 common European foods. This reference database was matched to foods and decomposed recipes obtained from country-specific validated dietary questionnaires in EPIC and intake levels of CEL, CML, and MG-H1 were estimated. Associations between dietary AGEs intake and body weight change were estimated separately for each of the three AGEs using multilevel mixed linear regression models with center as random effect and dietary AGEs intake and relevant confounders as fixed effects. Results: A one-SD increment in CEL intake was associated with 0.111 kg (95% CI 0.087–0.135) additional weight gain over 5 years. The corresponding additional weight gain for CML and MG-H1 was 0.065 kg (0.041–0.089) and 0.034 kg (0.012, 0.057), respectively. The top six food groups contributing to AGEs intake, with varying proportions across the AGEs, were cereals/cereal products, meat/processed meat, cakes/biscuits, dairy, sugar and confectionary, and fish/shellfish. Conclusion: In this study of European adults, higher intakes of AGEs were associated with marginally greater weight gain over an average of 5 years of follow-up.